The Role of The Qualification Certification Centers For Agricultural Employees in Buzau County, Romania - Beatrice-Simona MANOLACHE; Constantin MANOLACHE; Silvius STANCIU (Communications of International Proceedings, 2022)
The concept of a Center for the evaluation and certification of professional competences obtained in other ways than the formal ones, is a relatively new one and often confused with the Adult Vocational Training Center. Both target other forms of education but are subject to different rules of operation, the result being the same, namely diplomas of qualification recognized at national level and not only. The importance of the qualification of human resources in the agricultural field has increased considerably at the same time with the increase in the absorption level of European funds and through the phenomenon of constraint through the access conditions existing in the implementation guides, but also through the need to increase the level of qualification of the persons employed within the entities with agricultural profile, an adequate human resource being a safe way to admirable results. Buzau County is a landmark when analyzing the situation of the centers for the evaluation and certification of the professional competences obtained in other ways than the formal ones and their impact on the qualifications in the national agricultural field.
Keywords: qualification; agriculture; ANC Romania (National Qualifying Authority of Romania)